Perceived barriers to the effective management of diabetes mellitus among the Wakhi people: A qualitative study - Nazia Hassan (Kufa Journal for Nursing Sciences)
Self-management is one of the effective strategies used to maintain glucose levels and prevent complications associated with diabetes. It is the diabetic's responsibility to manage their chronic condition. The management includes monitoring blood glucose levels, taking diabetic medication as prescribed, adhering to a diabetic diet plan, and focusing on physical activity to maintain a healthy blood glucose level. These practices are necessary for the self-management of the disease; however, patients cannot self-manage their disease due to various obstacles.